Flow characteristics and sediment transport in a channel with emergent flexible vegetation - Montakhab, Amir (2012)
The effect of vegetation on open channel hydraulics is evident through the magnitudes, the profiles of the flow depth and the velocity, which relate to the plant characteristics. A number of vegetation characteristics affect the flow. Among these parameters, vegetation density is the key factor that contributes to the flow behavior and resistance in the vegetated channel. However, in current research practices, vegetation density only covers the number of vegetation and not the other physical characteristics. In reality, natural aquatic vegetation is herbaceous in nature and diverse in characteristics, so the determination of vegetation density in terms of number may be very difficult. For a solution, vegetation porosity which is based on the vegetation volume is suggested. Thus, this study aims at acquiring a practical method for porosity measurement, and applying it to the study of the effect of emergent flexible vegetation to velocity distribution, turbulence characteristics and sediment transport in continuous and discontinuous distributions of vegetation in a channel. This study consists of three main parts. In the first part of the study, several porosity measurement methods based on vegetation frontal area (two-dimensional) and vegetation volume (three-dimensional) were applied to estimate the porosity of vegetation (Lepironia articulata) in a laboratory flume for various flows and vegetation characteristics. The aim is to explore several methods, and hence, to suggest a method that is practical and accurate for vegetation porosity estimation, as well as to derive the relationships between porosity, velocity and flow depth. Velocity measurements using Acoustic Doppler Velocimeter (ADV) were made at different spatial locations along the flume, and the effects of varying incident flow rates (0.16–0.32ms-1) and vegetation porosity (88-96%) were investigated. The volumetric method for porosity measurement, which considers the fraction of the actual volume of the vegetation to the volume of water, is considered as more practical and accurate than the other methods. It was found that by assuming the vegetation as cylindrical in shape and considering only the frontal area of the most upstream vegetation, the porosity could be underestimated in average by 14%. However, the digital image analysis gave porosity difference of only 5%. From the laboratory data, correlations between the mean velocity, water depth and vegetation porosity were established. It was observed that by reducing the vegetation porosity by 8% would results in the velocity being reduced between 35% and 60% depending on the flow rate. The second part of the study explores the effect of porosity of vegetation patches on the velocity distribution and turbulent characteristics of flows that encounter them. It was observed that the flow encountering a single patch formed a turbulent wake at the downstream of vegetation, which then intensified the Reynolds stress and increased turbulence and sediment transport rate. Within this wake, the Reynolds stress increased downstream initially, reached the maximum and then decayed. The location of the maximum point of Reynolds stress was observed to be dependent on the vegetation porosity and flow rates. When the second patch was positioned within the region where the Reynolds stress was maximum, the Reynolds stress was decreased between 50% and 25% depending on vegetation porosity and flow rate. The patches revealed great performance in reducing the Reynolds stress at lower velocity and lower porosity. To sum up this part, flow and turbulence characteristics depend on the vegetation porosity and the distance between patches. In the final part of the study, sediment transport through continuous and patch vegetations was studied at different porosities and flow conditions. Water samples were collected from several locations along the channel, and the total suspended solid (TSS) test was applied for sediment trapping measurement. The results showed that porosity, location of patches and flow rate had a significant effect on the sediment transport. In addition, it was observed that the sediment transport in the vegetation channel was reduced up to 70% depending on the porosity value. The vegetation in patches could increase trapping sediment up to 90%. The results suggest that the patchy vegetation system is more efficient in reducing the Reynolds stress as well as sediment transport compared to continuous distribution. Finally, it can be concluded that porosity is an important component and it significantly affects velocity, turbulence and sediment transport in a vegetated channel.